1984
DOI: 10.1007/bf00393412
|View full text |Cite
|
Sign up to set email alerts
|

Regulation by sulfhydryl groups of glyceollin accumulation in soybean hypocotyls

Abstract: Hypocotyls of 5-d-old etiolated soybean seedlings (Glycine max (L.) Merr. cv. Altona) were treated with (a) dithiothreitol (DTT) or one of the sulfhydryl-binding reagents N-ethylmaleimide (NEM), p-hydroxymercuribenzoate (PMB) und p-chloromercuribenzene sulfonic acid (PMBS), (b) one of the sulfhydryl reagents in combination with DTT, (c) sulfhydryl reagent subsequent to treatment with DTT, and (d) PMBS followed by DTT. Glyceollin was extracted 24 and 48 h after initiation of treatment. The order of decreasing g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
18
0

Year Published

1985
1985
2001
2001

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 24 publications
2
18
0
Order By: Relevance
“…A wide range of organic and inorganic sulfhydrylmodifying reagents possess elicitor activity in various plant species (see, for example, Yoshikawa, 1978;Ingham et al, 1981;Osman and Fett, 1983;Stossel, 1984), although the effects of these molecules on elicitation in soybean appear to be indirect . Due to these activities, the biological sulfhydryl molecule glutathione has also been investigated as a potential defense-related signal.…”
Section: Gsh Partially Restores Elicitor Competencymentioning
confidence: 99%
“…A wide range of organic and inorganic sulfhydrylmodifying reagents possess elicitor activity in various plant species (see, for example, Yoshikawa, 1978;Ingham et al, 1981;Osman and Fett, 1983;Stossel, 1984), although the effects of these molecules on elicitation in soybean appear to be indirect . Due to these activities, the biological sulfhydryl molecule glutathione has also been investigated as a potential defense-related signal.…”
Section: Gsh Partially Restores Elicitor Competencymentioning
confidence: 99%
“…Moreover, certain sulfhydryl reagents stimulate the production of phytoalexins and the activation of other defense responses associated with the expression of disease resistance (11,24). Taken together these observations suggest that glutathione may play a role in mediating the response of plant cells to biological as well as physical stresses.…”
mentioning
confidence: 91%
“…Moreover, certain sulfhydryl reagents stimulate the production of phytoalexins and the activation of other defense responses associated with the expression of disease resistance (11,24). Taken …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…glyceollin) accumulation in fully developed soybean plants (15,16). Stossel (24,25) also showed that sulfhydrylbinding reagents could induce glyceollin accumulation in soybean hypocotyls. Glyceollin is one of several isoflavonoids in legumes that have been confirmed as contributors to the plant's antixenosis and antibiosis to insects (5,6,20,22).…”
mentioning
confidence: 98%